Psychosocial predictors of acceptance of voluntary counselling and testing among women of childbearing age in Ibadan metropolis (2011)
In order to get an optimal response from people in favour of VCT patronage, or usage, it is necessary to study the psychosocial predictors of acceptance of voluntary counselling and testing. Some of these factors include age, educational qualification and knowledge of VCT. This study examined how some psychosocial factors predict the practice of VCT among women in their childbearing age in Ibadan metropolis. Two hundred respondents participated in the research, 66 of which were market women, 60 were involved in various vocations and 74 were civil servants. Pearson correlation and multiple regression analyses were used in testing hypotheses. It was observed that knowledge of HIV, attitude to VCT, knowledge of VCT, fear of discrimination, respondents’ age, occupation, marital status and educational qualification have significant linear relationships with the practice of VCT, p<0.01. Also the independent variables accounted for 75% of the variance in respondents’ practice of VCT and the most potent contributors to the prediction of VCT practice were the knowledge of HIV (t = 6.04; p<0.01) followed by knowledge of VCT (t = 4.04; p<0.01), type of occupation (t = 3.98; p<0.01) and religion (t = -2.51; p<0.05). The study also revealed that the practice of VCT was quite low (29.0%). It was concluded that the public enlightenment on HIV and VCT should be intensified in order to enhance the practice of VCT among women.